2010
DOI: 10.1099/jmm.0.015644-0
|View full text |Cite
|
Sign up to set email alerts
|

Disease burden due to Streptococcus dysgalactiae subsp. equisimilis (group G and C streptococcus) is higher than that due to Streptococcus pyogenes among Mumbai school children

Abstract: Disease burden due to Streptococcus dysgalactiae subsp. equisimilis (group G and C streptococcus) is higher than that due to Streptococcus pyogenes among Mumbai school children Streptococcus pyogenes [group A streptococcus (GAS)], a human pathogen, and Streptococcus dysgalactiae subsp. equisimilis [human group G and C streptococcus (GGS/GCS)] are evolutionarily related, share the same tissue niche in humans, exchange genetic material, share up to half of their virulence-associated genes and cause a similar spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
64
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 27 publications
3
64
0
3
Order By: Relevance
“…A considerable increase in human infections associated with SDSE has been reported since the end of the last decade and studies have shown that the incidence of these isolates is similar to or even exceeds that of S. pyogenes in some countries (Bramhachari et al, 2010;Broyles et al, 2009). Despite our having analysed a convenience collection, the data clearly revealed some new and important information about SDSE.…”
Section: Discussionmentioning
confidence: 85%
“…A considerable increase in human infections associated with SDSE has been reported since the end of the last decade and studies have shown that the incidence of these isolates is similar to or even exceeds that of S. pyogenes in some countries (Bramhachari et al, 2010;Broyles et al, 2009). Despite our having analysed a convenience collection, the data clearly revealed some new and important information about SDSE.…”
Section: Discussionmentioning
confidence: 85%
“…Sin embargo, los casos de faringitis estreptocóccica fueron en su mayoría provocadas por S. pyogenes, lo que abre un debate en relación al rol patogénico de SDSE en la enfermedad estreptocóccica y post-estreptocóccica 4,10 . El diagnóstico microbiológico se realiza por la evidencia de hemólisis en placas de agar sangre y la identificación de los antígenos C y G. Sin embargo, hay que diferenciarlo de Streptococcus del grupo anginosus, lo que se logra con la reacción de Voges-Proskauer.…”
Section: Discussionunclassified
“…SDSE is a common colonizer of the oral and pharyngeal mucosa in children (15). It is classically considered a commensal of mucosae and the burden of disease is under recognized (16).…”
Section: Discussionmentioning
confidence: 99%